The environments of reproductive and birth defects research in the U.S. and West Germany (c. 1955-1975) - Nemec, Birgit; Dron, Heather (Studies in history and philosophy of science, 2022)
Most historiographies of the crossroads of environmental and reproductive health in 20th century start and end with the case of thalidomide. Despite its global scope, thalidomide today stands for sharp contrasts: in the numbers of victims, in institutional responses to the disaster, and also-more generally-in regulatory approaches to potential risks and national cultures of reproductive justice and disability rights. This paper takes a closer look at two countries that have been seen as emblematic of this divide in regulatory frameworks, despite similarities and interconnections in other areas, such as (pharma)industrial production, science, and robust feminist environmental health movements: the U.S. and West Germany. It argues that thalidomide needs to be historically contextualized within a broad framework of concepts and models of environment from research on exogenous reproductive effects. To do so, it reconstructs what counted as environment in research on reproductive health and birth defects in these two national settings in the postwar decades. It looks at transformations made across multifaceted initiatives, studying collective landscapes and workplaces as potentially dangerous "outer worlds," as well as smaller scale and more individualized environments, i.e., the maternal metabolism, uterus, lifestyle, or social interactions. The article thereby aims to explicate concepts and debates about the environment that influenced later national divisions in politics of science and technology, hinting of the democratic challenges these posed.
Gesehen am 08.03.2023